2014
DOI: 10.12968/ijtr.2014.21.9.410
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of walking for individuals with schizophrenia spectrum disorders: A systematic review

Abstract: Aim: Walking is a popular type of physical activity in individuals with schizophrenia – yet the benefits remain unclear. The aim of this review was to investigate if walking can a) reduce weight and b) have a positive influence on other health parameters in individuals (aged 16 years and over) with schizophrenia spectrum disorders in in- or outpatient settings. Methods: A systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyse (PRISMA) statement was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 38 publications
4
59
1
2
Order By: Relevance
“…In the same way, future research is needed to investigate whether brain health in people with schizophrenia is activity-dependent [24]. Recent systematic reviews of qualitative research considering the lived experience of patients have demonstrated that engaging in physical activity can improve confidence, reduce feelings of isolation and have a number of other important positive influences on bio-psychosocial outcomes [31,32]. Moreover, future research should explore the effects of physical activity interventions on other clinically relevant outcomes including inflammatory markers [10], pain [33], osteoporosis [34] and the risk for falls and fractures [35].…”
Section: Discussion Of the Top 10 Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, future research is needed to investigate whether brain health in people with schizophrenia is activity-dependent [24]. Recent systematic reviews of qualitative research considering the lived experience of patients have demonstrated that engaging in physical activity can improve confidence, reduce feelings of isolation and have a number of other important positive influences on bio-psychosocial outcomes [31,32]. Moreover, future research should explore the effects of physical activity interventions on other clinically relevant outcomes including inflammatory markers [10], pain [33], osteoporosis [34] and the risk for falls and fractures [35].…”
Section: Discussion Of the Top 10 Research Questionsmentioning
confidence: 99%
“…The current evidence is conflicting, for example, while Vancampfort et al [13] found an association between greater time spent sitting and a higher body mass index, Janney et al [72] did not find such association. In the general population, there is undeniable, rigorous evidence that sedentary behavior is, independent of physical activity associated with cardiovascular disease mortality [75].…”
Section: How Can We Prevent Sedentary Behavior In People With Schizopmentioning
confidence: 99%
“…Our data suggest that increasing daily steps might be an important strategy to mitigate metabolic risk in people with established psychosis. Moreover, walking is known to be a favored strategy for physical activity among people with schizophrenia and confers good health benefits [33,34]. Therefore, the combined message of 'sitting less and walking more' might offer health benefits for people with psychosis [35].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The physical health of individuals with schizophrenia is greatly much worse than that of the general population [6,8] and mortality rates remain persistently high, around twice that of the general population [1].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with schizophrenia are unlikely to decrease weight in response to exercise interventions [8]. For patients with depression, one trial found no weight reducing effect of exercise participation; however, a reduction of waist circumference was found in the intervention group [14].…”
Section: Discussionmentioning
confidence: 99%